(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
This research aims to analyze the speaking ability of female students of English Department in the third semester at Al-Asmarya Islamic University, faculty of Arts, academic year 2022/2023. Pronunciation and articulation are crucial components of effective spoken communication in any language, including English. This study focuses on the analysis of speaker voice, including pronunciation and articulation, which are criteria adopted by Lucas, (2012) and Gregory (1990) for analyzing female students of English language. The objectives of this study is firstly, to determine whether or not female students have speaking ability in pronunciations T, Linking and Reductions in the sentences in English conversations. Secondly, to put forward some suggestions and recommendations which can be useful for specialists and students to improve speaking skill in pronunciations. The descriptive research concentrated on statistical analysis of speaking ability of female students of English language department. The participants of the research were twelve female students of English language department and the data were collected through voice recordings of female students of English on Telegram as one of speaking assignments, then the researcher assessed their speaking ability in pronunciations through listening fifteen sentences which have boundaries of pronunciations and taken from three conversations from the textbook, then they measured into three levels which categorized into lower, middle and upper. The result revealed that the female students’ speaking ability of English language department at the faculty of Arts categorized into "lower" in pronunciations T, Linking and Reductions in the sentences in English conversations. The average score accomplished was -.64791- 80%; so that, the female students need more improvement, training and encouragement in pronunciations.